A multiregional general equilibrium model of the Austrian economy: Effects of the catch-up process of the CEECs on the regional economy - Martin Schneider (European Regional Science Association (ERSA), 1998)
This paper developes the first multiregional computable general equilibrium model for the Austrian economy. The model is based on an Arrow-Debreu-equilibrium. It contains the 9 Austrian Federal Provinces (NUTS-II) which are linked by trade flows with two groups of foreign countries (CEEC-4; ROW). The influence economic growth in the CEEC's has on the domestic economy is modelled by shifts of the import-demand and export-supply functions of the CEEC's. Simulation results show how the structural and welfare effects differ for the Austrian regions. Structural composition and geographic distance both affect regional results. JEL classification: C68, F11, F15, R13 Keywords: CGE modeling, regional model, catch-up, Austria, Eastern Europe
Keywords: 330